Advances in Electrochemical and Catalytic Performance of Nanostructured FeCo2O4 and Its Composites. Issue 19 (19th August 2021) - Shetgaonkar, Sarvesha S.; Salkar, Akshay V.; Morajkar, Pranay P.
Abstract: It is well established that the excessive and uncontrolled use of fossil fuels and organic chemicals have put a risk to the earth's environment and the life that sustains within it. Carbon‐free, sustainable, alternative energy technologies have therefore become the prime focus of current research. Smart inorganic materials have emerged as the potential solution to suffice energy needs and remediate the organic pollutants discharged to the environment. One such promising, versatile material is FeCo2 O4 which has gained immense research interest in the present decade due to its high efficiency and performance in energy and environmental applications. Innovative material design strategies involving the interplay of nanostructured morphology, chemical composition, redox surface states, and defect engineering have significantly enhanced both electrochemical and catalytic properties of FeCo2 O4 . Therefore, this review article aims to provide the first‐ever comprehensive account of the latest research and developments in design‐synthesis strategies, characterization techniques, and applications of nanostructured FeCo2 O4 and its composites in various electrochemical as well as catalytic applications. A detailed account of the nanostructured FeCo2 O4 and its composites in various energy storage and conversion devices such as supercapacitors (SCs), batteries, and fuel cells has been presented. Furthermore, a special section has been devoted to highlight the role of FeCo2 O4 in enhancing the sluggish reaction kinetics of oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in water splitting application. This review also highlights the role of nanostructured FeCo2 O4 in photocatalytic waste water treatment, gas sensing, and dual‐phase membrane technologies wherein FeCo2 O4 has demonstrated promising performance. Abstract : TOC graphic summarizing the numerous applications of FeCo2 O4 highlighted in this review. Adapted with permission from Ref. [54]. Copyright 2014 American Chemical society, Ref. [64]. Copyright 2018 Elsevier, Ref. [70]. Copyright 2017 Springer Nature, Ref. [95]. Copyright 2020 Elsevier, Ref. [112]. Copyright 2020 Elsevier, Ref. [126]. Copyright 2017 Elsevier and Ref. [87]. Copyright 2015 American Chemical Society.